Effect of Feeding Programs on Broilers Cobb and Arbor Acres plus Performance - Saki, A.A.; Momeni, M.; Tabatabaei, M.M.; Ahmadi, A.; Rahmati, M.M.H.; Matin, H.R. Hemati; Janjan, A. (International Journal of Poultry Science, 2010)
The main objective of this study was to determine the effects of various feeding programs (with different energy protein levels) and strain on broiler performance. Three hundred ninety six day old chicks were used in this study. The treatments groups were designed in a 2 x 3 factorial with two commercial strains (Cobb and Arbor Acres Plus) and three dietary programs 1) NRC regimen 2) Single diet (S) and 3) Phase Feeding Regimen (PF). Traits such as fed intake, feed conversion ratio, body weight, production index, mortality and growth rate were recorded for strains and feeding programs. At the end of period there were no significant effects between strains in mentioned traits. But for NRC and PF feed intake was significantly lower than S diet (p<0.05). Also NRC and PF diets significantly increased growth rate and average body weight comparing to S diet (p<0.05). NRC regimen, production index and feed conversion ratio were significantly better than PF and S diets (p<0.01). Except to feed conversion ratio at 42 days of age there were no significant interaction between strains and diets (p>0.05). S diet caused to decrees performance and economical efficiency. Decreasing diet cost and increasing economical efficiency were obtained by PF diet without any response in performance. It was concluded that better performance appeared by Arbor Acres Plus strain in regarding of NRC diet.